2016
DOI: 10.21608/ejnf.2016.74996
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Capsaicin Supplementation on Productive and Physiological Performance of Pekin Ducks During Summer Season

Abstract: he aim of this study was to evaluate the effect of using graded levels of capsaicin on growth performance, nutrients digestibility coefficients, serum metabolites, oxidative responses and intestinal digestive enzymes activity of Pekin ducks. One hundred and twenty 14d old Pekin ducks were randomly divided into four groups of 30 ducks. The first group was fed on the basal diet (control), while groups 2, 3 and 4 were given the basal diet supplemented with 50, 100 and 150 ppm capsaicin, respectively. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
1
3
0
1
Order By: Relevance
“…In the current study, the capsicum supplemented diet was observed to increase ADG. In agreement with our results, although in different species, capsaicin supplementation at 150 ppm increased body weight gain in Pekin ducks [ 38 ]. El-Tazi [ 39 ] also reported that 0.5%, 0.75% and 1% capsaicin inclusion in broiler chicks’ diet improved body weight gain and feed conversion ratio.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, the capsicum supplemented diet was observed to increase ADG. In agreement with our results, although in different species, capsaicin supplementation at 150 ppm increased body weight gain in Pekin ducks [ 38 ]. El-Tazi [ 39 ] also reported that 0.5%, 0.75% and 1% capsaicin inclusion in broiler chicks’ diet improved body weight gain and feed conversion ratio.…”
Section: Discussionsupporting
confidence: 92%
“…Capsaicin was reported to increase lipase secretion in rats [ 58 ]. Oh et al [ 16 ] reported that capsaicin supplementation in dairy cows increased the apparent total-tract digestibility of DM, OM and CP, but Ali et al [ 38 ] found no effect of capsaicin supplementation on CP digestibility. The discrepancies in the results may be due to differences in the capsaicin dosage or the formulation used [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The contents of TP and albumin in serum reflect the absorption and utilization of protein in animals, and the UN content is inversely correlated with that (Donsbough et al, 2010). The results indicated the negative effect of cooked chilli oil on protein catabolism, which contradicts the conclusion of Alagawany et al (2020), and capsaicin is directly responsible for the significant increase in serum glucose levels by increasing glycogen phosphorylase activity and thus accelerating glycogen decomposition (Spiridonov, 1994) component analysis similar to the results of relevant experiments on rats (Slowing et al, 2001), rabbits (Abdelnour et al, 2018) and Peking ducks (Ali et al, 2016). In addition, allicin may convert cholesterol to cholesterol-7α-hydroxylase to affect cholesterol homeostasis (Konjufca et al, 1997) and capsaicin may decrease blood lipid by decreasing cholesterol metabolism genes in the liver and increasing ileal bile acid metabolism genes (Li et al, 2019).…”
mentioning
confidence: 95%
“…Capsaicin contributes to most of the antimicrobial and antioxidant activity in capsicum (Elwan et al, 2020). In previous studies, researchers used cold-pressed chilli oil (Alagawany et al, 2020) or chilli powder (Jiang et al, 2019), which had some effects on feed intake, gut flora, fat digestion of poultry (Ali et al, 2016). The cooked chilli oil was rarely used in poultry and its feed intake promoting effect on pigeons was discovered unexpectedly, we decided to mix garlic oil and cooked chilli oil to apply in pigeon production.…”
mentioning
confidence: 99%
“…Досить виражений позитивний ефект отримали у дослідженнях [23] унаслідок додавання до кормів капсаїцину (екстракту перцю чилі) при вирощуванні пекінських качок. Зокрема, у разі додавання до раціону 14 добових пекінських качок 100 та 150 мг капсаїцину відзначається значне збільшення живої маси, коефіцієнта засвоюваності кормів (особливо за згодовування ефірного екстракту перцю чилі), значне підвищення активності амілази, ліпази та трипсину в усіх відділах тонкого кишківника, а також покращення мікробіологічного профілю шлунково-кишкового тракту.…”
unclassified